Studi Kritis Argumentasi Quraniyyun dalam Buku Hadits: Satu Penilaian Semula Karya Kassim Ahmad - Jajang Hidayatulloh; Engkos Kosasih; Muh. Arbiyansyah Nur (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This article discusses the views of the Qur'aniyyun, a group that recognizes only the Qur'an as the sole source of law, rejecting the authority of Hadith. One of their prominent figures, Kassim Ahmad, in his book Hadith: A Re-evaluation, presents arguments that challenge the validity of Hadith. This research aims to critically examine these arguments using content analysis and library research methods, providing a systematic and structured refutation. Kassim Ahmad's arguments center on an exclusive understanding and interpretation of the Qur'an, without incorporating Hadith. This stance creates confusion among Muslims regarding the position of Hadith as a source of law. This article asserts that such a view is unacceptable because Hadith plays a vital role in explaining and complementing the laws found in the Qur'an. Therefore, Hadith cannot be separated from the Qur'an in the context of Islamic law.